Exploring the relationship between baseline physical activity levels and mortality reduction associated with increases in physical activity: a modelling study. Issue 10 (18th October 2013) - Minton, Jonathan; Dimairo, Munyaradzi; Everson-Hock, Emma; Scott, Emma; Goyder, Elizabeth
Abstract : Background: Increasing physical activity (PA) levels among the general adult population of developed nations is important for reducing premature mortality and the burdens of preventable illness. Assessing how effective PA interventions are as health interventions often involves categorising participants as either 'active' or 'sedentary' after the interventions. A model was developed showing that doing this could significantly misestimate the health effect of PA interventions. Methods: A life table model was constructed combining evidence on baseline PA levels with evidence indicating the non-linear relationship between PA levels and all-cause mortality risks. PA intervention scenarios were modelled which had the same mean increase in PA but different levels of take-up by people who were more active or more sedentary to begin with. Results: The model simulations indicated that, compared with a scenario where already-active people did most of the additional PA, a scenario where the least active did the most additional PA was around a third more effective in preventing deaths between the ages of 50 and 60 years. The relationship between distribution of PA take-up and health effect was explored systematically and appeared non-linear. Conclusions: As the health gains of a given PA increase are greatest among people who are most sedentary, smaller increases in PA in the least active may have the same health benefits as much larger PA increases in the most active. To help such health effects to be assessed, PA studies should report changes in the distribution of PA level between the start and end of the study.